Mobilizing New York : AIDS, Antipoverty, and Feminist Activism - Carroll, Tamar W. (Book collections on Project MUSE., 2015)
Examining three interconnected case studies, Tamar Carroll powerfully demonstrates the ability of grassroots community activism to bridge racial and cultural differences and effect social change. Drawing on a rich array of oral histories, archival records, newspapers, films, and photographs, Carroll shows how poor people transformed the antipoverty organisation Mobilization for Youth and shaped the subsequent War on Poverty.